Heavy hitter : a novel - Cotugno, Katie (Harper, an imprint of HarperCollins Publishers, 2024)
"The beloved New York Times bestselling author of Birds of California hits it out of the park with this smart, sexy, thrilling take on the celebrity-athlete story--a funny, sizzling, ripped-from-the-headlinses romance between an international pop star and a major league baseball player who thought his best days were behind him"--